Guardians of the Buddha's home: domestic religion in the contemporary Jōdo Shinshū - Starling, Jessica (Contemporary Buddhism, 2019)
A family of clerics -- Staying at home as Buddhist propagation : the domestic life of the temple -- Home economics : stewardship of the Buddha's goods -- Social networks and social obligations in the disciplining of bōmori -- Wives in front of the altar -- Equality and freedom in the Ōtani-ha